Metodologia para seleção de fontes de resistência e obtenção de famílias de meloeiro resistentes à rizoctoniose - Silva, Gérffeson Thiago Mota de Almeida (2019)
Rhizoctoniosis, caused by the fungus Rhizoctonia solani Kühn, is among the most common diseases in melon crops. The use of resistant cultivars is one of the most strategically efficient measures for the integrated management of this disease, providing benefits to the environment, the producer and the consumer. Thus, the objective of this work was to develop an efficient methodology for the selection of R. solani resistant melon germplasm, as well as to identify resistance sources and obtain promising strains. The experiments were conducted under greenhouse conditions at the Embrapa Agroindústria Tropical’s Laboratory of Plant Breeding and Genetic Resources in Fortaleza, CE. For the development of the methodology of evaluation of rhizoctoniosis in melon crops, five experiments were conducted with the purpose of defining container, conduction environment, substrate for inoculum production, severity of different isolates, ideal inoculum density, inoculation method, phenological stage and time for evaluation after the inoculation. Thirty - two accessions were evaluated, from the Melon Germplasm Active Banks of Embrapa Hortaliças and Cucurbitáceas for the Brazilian Northeast of Embrapa Semiárido, and later, S1 families. These S1 families were obtained from the self-fertilization of highly resistant plants among the evaluated accessions, following the principles of the genealogical improvement method. The severity was estimated by means of a grade scale, ranging from: 1 - absence of symptoms; 2 - hypocotyl with small lesions (também pode ser “wounds”); 3 - hypocotyl with large lesions without constriction; 4 - totally constricted hypocotyl and 5 - seedlings. The average severity (SV) of the genotypes was used to group the genotypes into the following resistance classes: AR - highly resistant (SV = 1.0); R-resistant (1.1 <SV> 2.0); I - intermediate (2.1 <SV> 3.0); S - susceptible (3.1 <SV> 4.0); AS - highly susceptible (4.1 <SV> 5.0). The resistant plants frequency was also estimated by the ratio between the number of highly resistant plants (SV = 1.0) and the number of plants evaluated by genotype. Methods of grouping and analysis of Principal Components were used for differentiation and selection of genotypes. The results allow the recommendation of a methodology for evaluation of melon germplasm regarding the reaction to Rhizoctonia solani. This methodology consists of the recommendation on the use of seedlings with cutted roots in the transplanting for pots, containing sand with a sandy-organic inoculum in the concentration of 150 mg.kg-1 of soil, obtained from rice grains, associated with the inoculation with a hole in the stem of the plant per fungus-infested toothpick, conditioned without a humid chamber. Regarding the evaluation of the resistance of the melon germplasm, ten accessions were classified as resistant, with emphasis on BAGMEL 100, CNPH 15-276, BAGMEL 27, CNPH 15-446 and CNPH 93-692, which revealed lower means of severity and higher resistance frequencies, showing the potential for genetic improvement aiming at resistance to rhizoctoniosis. From the plants selected as highly resistant among the accessions, 16 S1 families were obtained, which have evidenced the efficiency of the selection process, with significant gains in relation to the average of the respective accesses from which they were selected. In this generation, the best families were CNPH 15-078_2, CNPH 11-233_1, CNPH 15-276_1, CNPH 16-439_1, CNPH 16-439_2, CNPH 15-446_2 and CNPH 93-689_4, from which the plants were selected to obtain the S1:2 families. Therefore, the established methodology was efficient to obtain superior genotypes, which aim at the introgression of resistance to rhizoctoniosis in elite genotypes of melon.